2007
DOI: 10.1111/j.1471-4159.2007.04843.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for polyamines in retinal ganglion cell excitotoxic death

Abstract: Neuronal death due to excessive activation of N-methyl-D-aspartate (NMDA) receptors is a hallmark of neurodegenerative diseases. The polyamines: putrescine, spermine, and spermidine, bind to specific sites on the NMDA receptor and promote its activation, but their role in NMDA-induced neuronal death is ill defined. In this study, we characterized the role of polyamines in excitotoxic death of retinal ganglion cells (RGCs), a population of central neurons susceptible to NMDAinduced damage. Our data show that en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 51 publications
(121 reference statements)
1
38
0
Order By: Relevance
“…Previously, it was reported that polyamines potentiate NMDA-triggered excitotoxicity. 42 However, we show that spermidine ameliorates retinal degeneration in the GCL. This discrepancy may be explained by various factors concerning experimental procedures including the route of polyamine administration, the nature of the molecules used (spermidine, putrescine, or spermine) and the dose.…”
Section: Discussionmentioning
confidence: 69%
“…Previously, it was reported that polyamines potentiate NMDA-triggered excitotoxicity. 42 However, we show that spermidine ameliorates retinal degeneration in the GCL. This discrepancy may be explained by various factors concerning experimental procedures including the route of polyamine administration, the nature of the molecules used (spermidine, putrescine, or spermine) and the dose.…”
Section: Discussionmentioning
confidence: 69%
“…Polyamines have multiple physiological and pathological functions including vascularization, tissue repair, and neural toxicity. [51][52][53] However, it is still questionable whether their function is proinflammatory or anti-inflammatory. 54,55 We have previously demonstrated that inhibiting NOX2/NADPH oxidase blocks inflammatory responses in mouse models of EIU and diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac cells, this ODC1 induction is caused by the activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2; also known as P42/P44 MAPK), and P13K/Akt pathways (Pernet et al, 2007; Zhang et al, 2014b). ODC1 activation by ERK1/2 is also dependent on Ca 2+ -mediated activation of calpain (Moldoveanu et al, 2002).…”
Section: Polyamines In Activity-feedback Mechanismsmentioning
confidence: 99%